PEMANFAATAN LIMBAH INDUSTRI TAHU SEBAGAI PAKAN ALTERNATIF UNTUK MENINGKATKAN PRODUKTIVITAS PETERNAK LELE - Bakhtiar; Khairul Anshar; Subhan; Syarifuddin (Politeknik Negeri Sriwijaya, 2022)
Catfish is one of the favorite foods of some Acehnese people, including for lhokseumawe region, and surrounding areas. This is what makes the community interested in cultivating catfish, in addition to the selling price is quite expensive as well as the demand for catfish that increases every year. To meet the increasing demand catfish breeders need the right feed to increase the growth rate of fish. This feed is a problem for farmers in the Lhokseumawe region because of the high price. The industry knows around Lhokseumawe quite a lot but industrial waste knows not to be utilized properly. Tofu waste in the form of tofu pulp can be used as catfish animal feed. The purpose of this devotional activity is to provide education and training to the community and catfish farmers in order to utilize industrial waste tofu as an alternative feed so as to solve the problem of too high feed prices. This devotional activity is carried out by providing counseling and technical guidance to the community so that it can make feed independently. Feed results showed the feed was able to float for 30-50 seconds and the fish showed interest in the feed. The cost aspect is known that the use of feed from tofu waste can reduce the cost of feed up to 50% with the calculation of the cost of the manufacturer's feed is Rp 18,000 / kg and feed from tofu pulp has a selling value of Rp 9,000, so the savings that occur are quite significant. Keywords: Fish Feed, Tofu Pulp, Catfish, Fermentation